Reviewing the therapeutic management of leprosy in primary care: demand case series referred to a University Hospital in the Midwest region of Brazil - Pétra Pereira de Sousa; Ana Lúcia Maroccolo de Sousa; Marília Dalva Turchi (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Leprosy still represents a negleted public health problem in Brazil. Early and adequate treatment of leprosy, carried out in a primary health network is essential to reduce morbidity and sequelae. Objective: To analyze the therapeutic management of leprosy patients referred from primary healthy services to a specialized service. Methods: An analytical retrospective study using medical records and the Notifiable Diseases Information System. Patients diagnosed with leprosy, referred to a specialized outpatient clinic, between 2016 and 2017, in Goiás state, were included. The treatment carried out in the primary health services was compared to the Ministry of Health guidelines. Results: Two-hundred twenty-five leprosy patients were included, of whom 33.3% were referred by leprosy reactions, 27.1% by sequelae, and 10.2% by suspected recurrence or reinfection. Reviewing the therapeutic management, 123 (54.7%) were considered inadequate, 92 (40.9%) adequate, and 10 (4.4%) inconclusive. Of the 200 multibacillary patients, 39.5% had adequate management. In contrast, 12 (85.1%) out of 14 paucibacillary patients had adequate management (χ2= 11.43 and p < 0.001). Regarding the leprosy reactions and sequelae management, 56.9% and 19.5% were considered inadequate, respectively. There was no difference between the percentage of adequate or inadequate management when considering the Goiás health macroregions (χ2= 7.23; 4 degrees of freedom; p = 0.12). Study limitations: Use of recorded data, with incomplete medical records and lack of patient follow-up. Conclusions: The study demonstrated the equivocal multibacillaryleprosy management conducted in healthy primary care, with an emphasis on leprosy reactions and sequelae. Training and monitoring the medical staff in the primary healthy services could reduce the morbidity and sequelae of leprosy.